Study of Contraceptive Use Among Comprehensive Abortion Care Clients in Family Planning Clinic of Tribhuban University Teaching Hospital - Bhandari, B R; Jha, R; Baral, J; Wagle, R R (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to assess the use of family planning method among comprehensive abortion care clients in Tribhuvan University Teaching Hospital (TUTH). Methods: A hospital based observational study was conducted in family planning clinic at TUTH from 14th April 2009 to 14th June 2010 among one hundred clients who opted for comprehensive abortion care (CAC) at the hospital CAC centre and met the inclusion criteria of this study. Results: Around 98% women had knowledge of different types of modern contraceptive methods. Majority of CAC clients (91%) had ever used contraceptive methods in the past. Injectables were the most common method of contraceptive used by the CAC clients (55%). Almost 22% clients had come for repeat induced abortion. About 43% clients opted CAC service for complete family and 33% for contraceptive failure. Withdrawal method failure was seen in 17% of clients. Almost 86% women intend to use contraceptive after CAC service in future. Conclusions: This study concluded that despite knowledge of modern contraceptive methods and ever uses of different family planning methods, majority of clients had no consistency in use of various contraceptives. Effective family planning counseling along with information of emergency contraceptive is required for each CAC clients to prevent unwanted pregnancy and abortion. DOI: http://dx.doi.org/10.3126/njog.v9i2.11740